MANAJEMEN LITERASI DIGITAL DALAM MENINGKATKAN MUTU PEMBELAJARAN SISWA SEKOLAH MENENGAH PERTAMA (SMP) (Studi Kasus di SMPN 1 Campaka Kabupaten Purwakarta) - Iva Khairun Nissa; Suci Indriany; N. Mumun Mulyawati; Uman Gunawan (STKIP Subang, 2026)
This study aims to describe digital literacy management in improving the quality of student learning at SMPN 1 Campaka. The research focuses on the planning, organizing, implementation, and evaluation of digital literacy, as well as its impact on learning quality. This study employed a qualitative approach using a case study method. The research participants consisted of the principal, teachers, and students. Data were collected through observation, interviews, and documentation. Data validity was ensured through source triangulation and technique triangulation, while data analysis followed the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings revealed that digital literacy management at SMPN 1 Campaka has been implemented through planning, organizing, implementation, and evaluation stages. The implementation of digital literacy utilizes various digital media, such as YouTube, Google Classroom, WhatsApp, and other digital platforms as learning tools. Digital literacy has a positive impact on learning quality, as reflected in increased student participation, motivation, understanding of learning materials, and independent learning skills. Although several challenges were identified, including limited digital devices, internet quotas, and network connectivity, the implementation of digital literacy generally supports more effective, interactive, and 21st-century-oriented learning processes.